Cell-mediated immune response to Leishmania chagasi experimental infection of BALB/c immunosuppressed mice - Machado, J. G. [UNESP]; Hoffmann, J. L. [UNESP]; Krause, V. L.K. [UNESP]; da Silva, A. V. [UNESP]; Dias-Melicio, L. A. [UNESP]; Langoni, H. [UNESP] (FapUNIFESP (SciELO), 2010)
Leishmaniasis, a zoonosis of worldwide distribution, presents a significant impact on immunosupressed patients. This study aimed to evaluate Leishmania chagasi infection in BALB/c mice immunosuppressed with dexamethasone. Spleen cells stimulated or not with L. chagasi were cultured for cytokine quantification (IFN-γ, IL-2, IL-4 and IL-10) by sandwich ELISA. Parasite loads in the spleen and liver were determined by means of culture microtitration. Immunosuppressed groups showed statistically lower spleen weight and CD4-cell percentage in blood on the day of infection and produced Th1 and Th2 cytokines on other days of the study. The other infected groups, weather immunosupressed or not, also produced Th1 and Th2 cytokines. Parasite loads in the spleen and liver were not statistically different among the groups. It was concluded that L. chagasi infection was not affected by dexamethasone-induced immunosuppression, probably due the reversible effect of the treatment.
Keywords: Immunopathology; Immunosuppression; Interleukins; Mice; Visceral leishmaniasis